Rehabilitasi Terhadap Korban Tindak Pidana Penyalahgunaan Narkotika Oleh Badan Narkotika Nasional Provinsi Jambi - Dedy Syaputra; Triamy Rostarum; Joan Rafli Alhamdi (Legalitas: Jurnal Hukum, 2025)
Drug abuse is a problem that continues to receive serious attention from various parties due to its continued increase over time. The regulation of narcotics in Indonesian law is comprehensively regulated through Law Number 35 of 2009 concerning Narcotics. The rehabilitation approach is also an important part of this regulation. The law requires drug addicts to undergo medical and social rehabilitation, as an effort to restore their condition so they can return to functioning optimally in society. This shows that the law is not only repressive, but also provides space for recovery. The purpose of this study is to determine and analyze the implementation of rehabilitation for victims of drug abuse crimes by the Jambi Province National Narcotics Agency (BNN) and to identify and analyze the obstacles faced by the Jambi Province BNN in implementing rehabilitation strategies for victims of drug abuse crimes. The method used in this study is an empirical juridical research method. Data collection in this study was conducted through interviews. From the results of this study, it can be concluded that the implementation of rehabilitation for victims of drug abuse crimes by the Jambi Province National Narcotics Agency (BNN) is carried out through medical rehabilitation, specifically outpatient treatment. During this process, victims receive counseling sessions aimed at assisting with psychological and social recovery. In implementing the rehabilitation program for drug abuse victims, the Jambi Provincial National Narcotics Agency (BNN) faces various obstacles. These include a lack of public awareness of the importance of rehabilitation, stigma and discrimination against victims, irregular client attendance during the rehabilitation process, legal issues experienced by some clients, and a lack of ongoing support after clients complete the rehabilitation program. By increasing public awareness, reducing stigma, fostering participant discipline, providing legal assistance, and strengthening post-rehabilitation programs, the Jambi Province BNN is trying to address these obstacles.